Ethnobotany, chemical analysis, and antiglycation activity of Elsholtzia species from Northern Thailand - Inta, Angkhana; Mungkornasawakul, Pitchaya; Shank, Lalida; Pongamornkul, Wittaya; Shi, Yinxian; Fu, Yao; Yao, Ruyu (Frontiers in Pharmacology, 2025)
Seven species of Elsholtzia from upper northern Thailand were ethnobotanically surveyed, and the plant parts utilized by local communities were collected for chemical analysis and antiglycation activity evaluation. The 80% methanol extracts were concentrated and analyzed for total soluble phenolic content using the Folin–Ciocalteu reagent, and phytochemical profiling was performed by high-performance liquid chromatography (HPLC) against standard phenolic compounds. In addition, the extracts were investigated for antiglycation activity using the methylglyoxal (MGO)-BSA method, with aminoguanidine as a positive control. According to the ethnobotanical survey, the seven Elsholtzia species were traditionally used as food, medicine, and insect repellents by seven ethnic groups: Akha, Hmong, Karen, Lawa, Lisu, Tai Lue, and Tai Yai. Most species were cultivated and commonly found in agricultural areas, including upland rice fields and home gardens. HPLC analysis identified three major phenolic compounds—rosmarinic acid, ferulic acid, and luteolin—showing species- and plant part-specific variations. The leaf extract of E. beddomei contained the highest rosmarinic acid (667.9 mg/100 g), E. griffithii exhibited the highest ferulic acid (2.25 mg/100 g), and luteolin was detected exclusively in E. stachyodes (15.4 mg/100 g). Consistently, E. beddomei also had the highest total phenolic content (36.04 mg GAE/g) and the strongest antiglycation activity, with an IC50 value of 1.65 mg/mL. The observed trend suggests that phenolic-rich extracts, particularly those with elevated rosmarinic acid content, are strongly associated with enhanced anti-glycation potential. These findings validate local ethnobotanical practices and highlight the species-specific potential of Elsholtzia as sources of bioactive compounds, supporting their further development for pharmaceutical and nutraceutical applications.